Fashion and Middle Age: female considerations of today’s clothing products (ModaPalavra e-periódico, 2016)
The dynamics of the fashion market drives forward many companies of the sector to delineate industrial and commercial strategies in order to ensure themselves against the competition. In addition, the easy access to the mass media has induced users and consumers more informed and aware about their need and expectations, which has increased the level of demand goods, mainly clothing. In this sense, this study aimed to identify and discuss the considerations of middle-aged women, in relation to clothing products currently found on the market as well as possible changes in their spending habits. To this end, a questionnaire was prepared and applied to a sample group of women between ages 45 and 65, aiming to clarify such issues. It is evident the importance of this segment of users, once they are a representative demand for the fashion industry.
Keywords: fashion; middle age; consumption